2006
DOI: 10.1523/jneurosci.0499-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dual Circuitry for Odor-Shock Conditioning during Infancy: Corticosterone Switches between Fear and Attraction via Amygdala

Abstract: Rat pups must learn maternal odor to support attachment behaviors, including nursing and orientation toward the mother. Neonates have a sensitive period for rapid, robust odor learning characterized by increased ability to learn odor preferences and decreased ability to learn odor aversions. Specifically, odor-0.5 mA shock association paradoxically causes an odor preference and coincident failure of amygdala activation in pups until postnatal day 10 (P10). Because sensitive-period termination coincides with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
236
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(250 citation statements)
references
References 104 publications
13
236
0
1
Order By: Relevance
“…Prior research suggests that developmental changes in cortisol (40,41) contribute to brain development through interactions with receptors that regulate genes involved in neuromaturational processes (42,43). Some of these maturational changes are specific to amygdala-mPFC circuitry, instantiated either through direct administration of glucocorticoids or via maternal absence (which elevates glucocorticoid levels) (5,8,15). We observed higher levels of cortisol, the primary glucocorticoid in humans, in the PI group, consistent with past findings in similar samples (44).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Prior research suggests that developmental changes in cortisol (40,41) contribute to brain development through interactions with receptors that regulate genes involved in neuromaturational processes (42,43). Some of these maturational changes are specific to amygdala-mPFC circuitry, instantiated either through direct administration of glucocorticoids or via maternal absence (which elevates glucocorticoid levels) (5,8,15). We observed higher levels of cortisol, the primary glucocorticoid in humans, in the PI group, consistent with past findings in similar samples (44).…”
Section: Discussionsupporting
confidence: 89%
“…Our interpretation that the observed mature-like negative amygdala-mPFC connectivity in PI children evidences accelerated development is supported by rodent models that have demonstrated causal relationships between maternal absence and acceleration of amygdala-mPFC phenotypes (5,15,17). Research in normative human development has shown that regulatory connections between the amygdala and mPFC manifest as positive coupling in childhood and shift to a mature pattern of negative coupling during adolescence (28).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our previous work has shown that FKBP5 'risk' polymorphisms that manifest with enhanced induction of FKBP5, altered cortisol release, and impaired negative feedback are associated with an increased risk to develop PTSD or related symptoms. Consistent with the ultra-short negative feedback between the FKBP5 protein and GR activation, genotype-mediated increases in FKBP5 transcription have been shown to be associated with GR resistance (Moriceau et al, 2006;Binder et al, 2008) and with a decreased efficiency of negative feedback of the stress hormone axes accompanied by prolonged cortisol release (Ising et al, 2008). The SNPs, rs3800373 and rs1360780, have been associated with increased peri-traumatic dissociation in children after medical trauma (Koenen et al, 2005) and higher levels of peri-traumatic dissociation have been shown to be predictors of PTSD in adults (Ozer et al, 2003).…”
Section: Discussionmentioning
confidence: 78%
“…The infant rodent amygdala is uniquely dependent upon stress hormones for engaging mechanisms for plasticity within the amygdala: the infant amygdala can be switched on and off simply based on the level of stress hormones with stress hormones being robustly controlled by the caregiver in early development (Barr et al, 2009;Moriceau, Wilson, Levine, & Sullivan, 2006;Shionoya et al, 2007;Thompson, Sullivan, & Wilson, 2008). Specifically, in rat pups, amygdala-dependent threat (fear) conditioning can be precociously induced by increasing systemic stress hormone corticosterone (analogous to cortisol in humans) by injecting pups, or through naturalistic means such as increasing pups' early life stress or by exposing pups to a mother releasing an alarm pheromone (Barr et al, 2009;Debiec & Sullivan, 2014;Moriceau et al, 2009).…”
Section: The Attachment Figure Guides Learning About the Worldmentioning
confidence: 99%